2013
DOI: 10.1007/s12013-013-9539-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of miR-21 on Renal Fibrosis by Regulating MMP-9 and TIMP1 in kk-ay Diabetic Nephropathy Mice

Abstract: MicroRNAs (miRs) play important roles in initiation and progression of many pathologic processes. However, the roles of miRs in diabetic nephropathy remain unclear. This study was to determine whether miR-21 was involved in diabetic nephropathy and to explore the relationship between miR-21 and MMP9/TIMP1 expression in diabetic nephropathy. In situ hybridization studies showed that miR-21 was primarily localized and distributed in cortical glomerular and renal tubular cells in diabetic kk-ay kidney. Real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(117 citation statements)
references
References 38 publications
4
110
0
3
Order By: Relevance
“…It has also been reported that MMPs, such as MMP2 and MMP9, participate in the degradation of the extracellular matrix (ECM), leading to tumor cell invasion (40). Additionally, MMPs are negatively regulated by TIMPs (41). In the present study, we detected the expression levels of proteins related to cell invasion (TIMP1, MMP2 and MMP9) in miR-214 mimic-transfected MCF-7 cells.…”
Section: Discussionmentioning
confidence: 67%
“…It has also been reported that MMPs, such as MMP2 and MMP9, participate in the degradation of the extracellular matrix (ECM), leading to tumor cell invasion (40). Additionally, MMPs are negatively regulated by TIMPs (41). In the present study, we detected the expression levels of proteins related to cell invasion (TIMP1, MMP2 and MMP9) in miR-214 mimic-transfected MCF-7 cells.…”
Section: Discussionmentioning
confidence: 67%
“…В модели ДН у мышей линии KK-Ay увеличение экспрессии miR-21 способствовало развитию почечного фиброза за счет влияния на экспрессию белков, регу-лирующих интенсивность расщепления компонентов ЭЦМ, -матриксной металлопротеиназы-9 и ингиби-тора матриксных металлопротеиназ 1 типа (TIMP-1) [40]. Chau B.N.…”
Section: сахарный диабет Diabetes Mellitusunclassified
“…Upregulation of miR-21 by TGF-b could promote ECM expansion and kidney fibrosis by silencing metabolic pathways, regulating MMP-9 and TIMP1 expression, and by activating PTEN/AKT/TORC1 signaling and other pathways. [13][14][15] TGF-b may elevate the miR-21 level by initiating the transcription of genes that encode the essential regulatory elements for miRNA maturation. Smad3 is an upstream molecule of miR-21 that executes TGF-b-induced tissue fibrosis.…”
Section: Introductionmentioning
confidence: 99%